[tex]1)=( \frac{15-1}{9} - \frac{5}{9} )*(- \frac{16-1}{9} ): \frac{5}{2} = \\ =( \frac{14}{9} - \frac{5}{9} )*(- \frac{15}{9} ): \frac{5}{2} = \\ = \frac{9}{9} *(- \frac{15}{9} ): \frac{5}{2} = \\ =1*(- \frac{15}{9} ): \frac{5}{2} = \\ =- \frac{15}{9} * \frac{2}{5} (simplificam.15.cu.5.prin.5)= \\ =- \frac{3}{9} * \frac{2}{1} =(simplificam.prin.3.pe.3.si.pe.9) \\ =- \frac{1}{3} * \frac{2}{1} = \\ =- \frac{2}{3} [/tex][tex]2)x+ \frac{2}{2} + \frac{1}{3} =2x- \frac{1}{6} \\ x-2x=- \frac{1}{6} - \frac{2}{2} - \frac{1}{3}(6.este.NC,amplificam) \\ -x=- \frac{1}{6} - \frac{6}{6} - \frac{2}{6} \\ -x=- \frac{9}{6} |*(-1) \\ x= \frac{9}{6} (siplificam.cu.3) \\ x= \frac{3}{2} [/tex]